Use of SPECT with {99m}Tc-Pyrophosphate Combined with a Perfusion Myocardium Scintigraphy in the Evaluation of Inflammatory Changes of the Heart in Patients with Persistent Atrial Fibrillation; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Sazonova S. I. Svetlana Ivanovna; Lishmanov Yu. B. Yury Borisovich; Iljyushenkova Yu. N. Yuliya Nikolaevna; Batalov R. E.; Rogovskaya Y. V. (Radiation Technologies in Medicine, 2015)
Title screen